2020
DOI: 10.1590/2175-7860202071051
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and biological assays of ethanolic leaf extract of Senna rugosa

Abstract: Senna rugosa (Fabaceae) is a common specie of the Brazilian territory, especially in the Cerrado biome. It is widely used in the popular medicine although not yet adequately investigated as to its phytoconstituents and pharmacological activities. In this study, the preliminary phytochemical analysis of ethanolic leaf extract of S. rugosa was performed and its cytotoxicity, antitumoral and antimicrobial activities (antibacterial, antifungal, anti-Trypanosoma and anti-Leishmania) were evaluated. The crude extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
3
1
1
Order By: Relevance
“…In the report by Cunha et al, [37] several peaks were observed in the hydroethanolic extract, but only one compound was identified (rutin), making comparison with our results impossible. Thus, we report the presence of different phytochemicals not previously described for this species.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In the report by Cunha et al, [37] several peaks were observed in the hydroethanolic extract, but only one compound was identified (rutin), making comparison with our results impossible. Thus, we report the presence of different phytochemicals not previously described for this species.…”
Section: Discussioncontrasting
confidence: 91%
“…Senna rugosa (Fabaceae) is a plant species popularly known as amendoirana, alcacuz bravo, bico-de-corvo, boi gordo and paratudo, where its seeds are used to treat parasitic worms' infestations [27,28] and its roots are used in the treatment of poisonous snake bites [29]. Recently, Cunha et al, [30] evaluated the chemical composition of the ethanolic extract of S. rugosa leaves and fractions obtained from the extract and identified the presence of mainly phenolic compounds, which include flavonols, anthraquinones and anthrones derivatives (particularly, rutin, emodin, aloe-emodin and barbaloin/isobarbaloin). In that study, antimicrobial, antifungal, and moderate antitumor activities against breast cancer cell lines were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening for secondary metabolites in the hydro-ethanolic extract of SP leaves was performed using standard phytochemical methods reported in the literature. 10 11 Results suggested that alkaloid, saponin, tannin, cardiac glycoside, flavonoid, anthraquinone, and phenol were present in the SP extract, while steroids were absent. Tannins, flavonoids, and phenols are potent antioxidants, and antioxidants have been implicated in wound healings by improving vascularization and reducing lipid peroxidation which in turn prevents necrosis of cells and promotes cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of alkaloids, saponins, tannins, steroids, cardiac-active glycoside, flavonoids, anthraquinones, and phenols in the extract was assessed respectively as the following according to the reported studies 10 11 :…”
Section: Methodsmentioning
confidence: 99%
“…A su vez, Matulevich et al, (2017), identicaron la presencia de avonoides, quinonas, alcaloides, taninos, glucósidos cardiotónicos y terpenos en extractos de Senna reticulata, estos resultados son congruentes con lo encontrado en S. birostris especialmente los avonoides, taninos, alcaloides y quinonas. Otro análisis toquímico preliminar desarrollado por Cunha et al, (2020), mostró la presencia de avonoides, taninos, triterpenos y antraquinonas en el extracto etanólico de las hojas de Senna rugosa. Por su parte, Isaac et al, (2022) en su reciente investigación encontraron que en el extracto etanólico de las hojas de Senna podocarpa, los principales metabolitos presentes fueron alcaloides, saponinas, taninos, glicósidos cardíacos, avonoides, antraquinonas y fenólicos.…”
Section: Discussionunclassified